2020
DOI: 10.3390/polysaccharides1010004
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS-Based Metabolomics Analysis of Prawn Shell Waste Co-Fermentation by Lactobacillus plantarum and Bacillus subtilis

Abstract: GC-MS-based metabolomics were used to investigate metabolic changes in prawn shell waste during fermentation. Microbial strains Lactobacillus plantarum and Bacillus subtilis were co-fermented in a shake flask comprising of 5% (w/v) prawn shell waste and 20% (w/v) glucose as a carbon source. Analysis of the prawn shell waste fermentation showed a total of 376 metabolites detected in the culture supernatant, including 14 amino acids, 106 organic acids, and 90 antimicrobial molecules. Results show that the liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 127 publications
1
0
0
Order By: Relevance
“…In 2020, the derivatives of Nonadecanoic acid, benzoic acid, hexadecanoic acid and pyrrol were separated from the Lactobacillus plantarum. The results of this research are in line with those reported here in [30]. We extracted LAB from ke r dough and tested its antibacterial properties against S. mutans and P. gingivalis bio lms.…”
Section: Discussionsupporting
confidence: 88%
“…In 2020, the derivatives of Nonadecanoic acid, benzoic acid, hexadecanoic acid and pyrrol were separated from the Lactobacillus plantarum. The results of this research are in line with those reported here in [30]. We extracted LAB from ke r dough and tested its antibacterial properties against S. mutans and P. gingivalis bio lms.…”
Section: Discussionsupporting
confidence: 88%